Comparative transcriptomics of immune checkpoint inhibitor myocarditis identifies guanylate binding protein 5 and 6 dysregulation - Finke, Daniel; Heckmann, Markus B.; Salatzki, Janek; Riffel, Johannes; Herpel, Esther; Heinzerling, Lucie M.; Meder, Benjamin; Völkers, Mirko; Müller, Oliver J.; Frey, Norbert; Katus, Hugo; Leuschner, Florian; et al. (Cancers, 2021)
Immune checkpoint inhibitors (ICIs) are revolutionizing cancer treatment. Nevertheless, their increasing use leads to an increase of immune-related adverse events (irAEs). Among them, ICI-associated myocarditis (ICIM) is a rare irAE with a high mortality rate. We aimed to characterize the transcriptional changes of ICIM myocardial biopsies and their possible implications. Patients suspected for ICIM were assessed in the cardio-oncology units of University Hospitals Heidelberg and Kiel. Via RNA sequencing of myocardial biopsies, we compared transcriptional changes of ICIM (n = 9) with samples from dilated cardiomyopathy (DCM, n = 11), virus-induced myocarditis (VIM, n = 5), and with samples of patients receiving ICIs without any evidence of myocarditis (n = 4). Patients with ICIM (n = 19) showed an inconsistent clinical presentation, e.g., asymptomatic elevation of cardiac biomarkers (hs-cTnT, NT-proBNP, CK), a drop in left ventricular ejection fraction, or late gadolinium enhancement in cMRI. We found 3784 upregulated genes in ICIM (FDR < 0.05). In the overrepresented pathway ‘response to interferon-gamma’, we found guanylate binding protein 5 and 6 (compared with VIM: GBP5 (log2 fc 3.21), GBP6 (log2 fc 5.37)) to be significantly increased in ICIM on RNA- and protein-level. We conclude that interferon-gamma and inflammasome-regulating proteins, such as GBP5, may be of unrecognized significance in the pathophysiology of ICIM.